Gendered geographies of environmental injustice - Buckingham, Susan; Kulcur, Rakibe (Antipode, 2009)
As environmental justice concerns become more widely embedded in environmental organizations and policymaking, and increasingly the focus of academic study, the gender dimension dissolves into an exclusive focus on race/ethnicity and class/income. While grassroots campaigning activities were often dominated by women, in the more institutionalized activities of organizations dominated by salaried professionals, gender inequality is neglected as a vector of environmental injustice, and addressing this inequality is not considered a strategy for redress. This paper explores some of the reasons why this may be so, which include a lack of visibility of gendered environmental injustice; professional campaigning organizations which are themselves gender blind; institutions at a range of scales which are still structured by gender (as well as class and race) inequalities; and an intellectual academy which continues to marginalize the study of gender—and women's—inequality. The authors draw on experience of environmental activism, participant observation, and other qualitative research into the gendering of environmental activity, to first explore the constructions of scale to see how this might limit a gender-fair approach to environmental justice. Following this, the practice of “gender mainstreaming” in environmental organizations and institutions will be examined, demonstrating how this is limited in scope and fails to impact on the gendering of environmental injustice.
Keywords: approches et analyses; corps; discipline; environnement; géographie; intersectionnalité; justice environnementale; justice sociale; projet charge mentale; sciences humaines; thématiques

Ces corps qui comptent : de la matérialité et des limites discursives du sexe - Butler, Judith (Éditions Amsterdam, 2009)
Traduction de Bodies That Matter, (1993) La prise en compte de la matérialité des corps n’implique pas la saisie d’une réalité pure, naturelle, derrière le genre : si le sexe est un présupposé nécessaire du genre, nous n’aurons jamais accès au réel du sexe qu’à travers nos schèmes culturels. Le sexe, comme le genre, est une norme culturelle, qui régit la matérialité des corps. Il importe donc de souligner que le concept de matière a une histoire, où sont sédimentés les discours sur la différence sexuelle. En outre, si certains corps (par exemple blancs, mâles et hétérosexuels) sont valorisés par la norme, d’autres (par exemple lesbiens ou non blancs) sont produits comme abjects, rejetés dans un dehors invivable. À travers une reprise critique du concept foucaldien de « contrainte productive », Judith Butler s’efforce, loin de tout volontarisme, de ressaisir la façon dont ces corps peuvent défaire les normes qui les constituent et devenir le lieu d’une puissance d’agir transformatrice. Ce livre, où l’épistémologie se mêle à la politique, constitue un jalon des études de genre et l’un des ouvrages majeurs de son auteure.
Donné en lecture a cours POL4212, « Critically Queer », pp 225-244.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; art contemporain; corps; cours; culture; discipline; fem1000; genre; hétérosexisme; identités LGBTQIA2+; lit4700; maternité; philosophie; pol4212; politique; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sexe; soc2014; systèmes d'oppressions; thématiques; épistémologie; épistémologie queer; états-unis; études culturelles

La matrice de la race: généalogie sexuelle et coloniale de la nation française - Dorlin, Elsa (La Découverte, 2009)
La race a une histoire, qui renvoie à l'histoire de la différence sexuelle. Au XVIIIe siècle, les discours médicaux affligent le corps des femmes de mille maux : « suffocation de la matrice » « hystérie », « fureur utérine », etc. La conception du corps des femmes comme un corps malade justifie efficacement l'inégalité des sexes. Le sain et le malsain fonctionnent comme des catégories de pouvoir. Aux Amériques, les premiers naturalistes prennent alors modèle sur la différence sexuelle pour élaborer le concept de « race » : les Indiens Caraïbes ou les esclaves déportés seraient des populations au tempérament pathogène, efféminé et faible. Ce sont ces articulations entre le genre, la sexualité et la race, et son rôle central dans la formation de la Nation française moderne qu'analyse Elsa Dorlin, au croisement de la philosophie politique, de l'histoire de la médecine et des études sur le genre. L'auteure montre comment on est passé de la définition d'un « tempérament de sexe » à celle d'un « tempérament de race ». La Nation prend littéralement corps dans le modèle féminin de la « mère », blanche, saine et maternelle, opposée aux figures d'une féminité « dégénérée » ? la sorcière, la vaporeuse, la vivandière hommasse, la nymphomane, la tribade et l'esclave africaine. Il apparaît ainsi que le sexe et la race participent d'une même matrice au moment où la Nation française s'engage dans l'esclavage et la colonisation.
OCLC: 755865532
Keywords: 1700-1799; approches et analyses; corps; cours; discipline; europe; france; histoire et politique; premier cycle; périodes historiques; représentation; représentation des femme*; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; sud global; système colonial; systèmes d'oppressions; thématiques; violences

De la servitude au travail de service : les continuités historiques de la division raciale du travail reproductif payé. - Glenn, Evelyn Nakano (Sexe, race, classe pour une épistémologie de la domination, 2009)
La pensée féministe s'est historiquement attachée, depuis – voire en dehors de – la tradition matérialiste, à montrer que le rapport de classe n'épuise pas l'expérience de la domination vécue par les femmes et, plus généralement, par les minorités sexuelles. Plus encore, en élaborant des outils d'analyse tels que le mode de production domestique , les rapports sociaux de sexe ou le rapport de genre , la pensée féministe a travaillé sur l'imbrication des rapports de pouvoir, dénaturalisant la catégorie de sexe à l'aune de ses déterminations historico-sociales. Depuis quelques années en France, la réflexion sur l'imbrication des rapports de pouvoir s'est complexifiée davantage, notamment sous l'influence des travaux nord et sud-américains, mais aussi caribéens ou indiens. Les problématiques relatives aux identités sexuelles, aux régimes de sexualité, mais aussi celles articulant le genre et la nation, la religion et/ou la couleur, ont permis de développer un véritable champ de réflexion. La question cruciale de l'articulation du sexisme et du racisme, notamment, a ainsi renouvelé tout autant l'agenda des mouvements féministes que la recherche universitaire. Cet ouvrage a pour but d'interroger les différents outils critiques pour penser l'articulation des rapports de pouvoir. Tout en interrogeant leur mode propre de catégorisation (les catégories de sexe et de race ont-elles méthodologiquement le même statut que la classe ? À quelles conditions utiliser la catégorie de race comme une catégorie d'analyse ? L'analyse en termes de classe a-t-elle été éclipsée par l'analyse croisée du sexisme et du racisme, après les avoir longtemps occultés ?...) cet ouvrage discute les différents modes de conceptualisation de ce que l'on pourrait appeler l'hydre de la domination : analogique, arithmétique, géométrique, généalogique. À partir de différentes traditions disciplinaires (sociologie, science politique, philosophie, psychologie, littérature...), les contributions ici réunies présentent un état des lieux des diverses appréhensions de l'imbrication des rapports de pouvoir – intersectionnalité , consubstantialité , mondialité , postcolonialité , ... et, ce faisant, (re)dessinent les contours d'une véritable épistémologie de la domination. (
Section: 1 vol. (313 p.) : couv. ill. ; 22 cm.
Keywords: 1900-1999; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminisme matérialiste; féminismes noirs; maternité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; soc1016; sociologie; système colonial; systèmes d'oppressions; thématiques; travail; travail reproductif; états-unis

Critical intersex - Holmes, Morgan (Ashgate, 2009)
To date, intersex studies has not received the scholarly attention it deserves as research in this area has been centred around certain key questions, scholars and geographical regions. Exploring previously neglected territories, this book broadens the scope of intersex studies, whilst adopting perspectives that turn the gaze of the liberal, humanist, scientific outlook upon itself, in order to reconfigure debates about rights, autonomy and subjectivity, and challenges the accepted paradigms of intersex identity politics. Presenting the latest theoretical and empirical research from an international group of experts, this is a truly interdisciplinary volume containing critical approaches from both the humanities and social sciences. With its contributions to sociology, anthropology, medicine, law, history, cultural studies, psychology and psychoanalysis, Critical Intersex will appeal to scholars and clinical practitioners alike.
Section: 1 vol. (XIV-257 p.) ; 24 cm.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; inégalités; premier cycle; queer; santé; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; violences; violences médicales; études intersexes

La philosophie du corps - Marzano, Michela (Presses universitaires de France, 2009)
Les philosophes ont souvent préféré méditer sur l’âme et ses passions, faire des enquêtes sur l’entendement humain, ou encore critiquer la raison pure, plutôt que de se pencher sur la réalité du corps et sur la finitude de la condition humaine. Pourtant, même si le corps a souvent été considéré comme un fardeau entravant la connaissance et la vertu, aucune philosophie n’a jamais pu faire l’économie de sa présence. C’est dans et avec son corps que chacun de nous naît, vit, meurt ; c’est dans et par son corps qu’on s’inscrit dans le monde et qu’on rencontre autrui. Michela Marzano analyse les paradoxes de notre rapport au corps et la manière dont chaque époque invite à le repenser.
Contenu: Présentation du statut ambigu du corps humain à travers cinq chapitres : Le dualisme et ses étapes ; Du monisme à la phénoménologie ; Le corps entre nature et culture ; Abjection et réification : l'opacité de la matière ; Sexualité et subjectivité : l'accomplissement de la chair.
Keywords: corps; cours; discipline; lit4700; philosophie; premier cycle; ressource en ligne; sciences humaines; sexualité; thématiques

Transformative conversations about sexualities pedagogy and the experience of sexual knowing - Trimble, Lisa (Sex Education : Sexuality, Society and Learning, 2009)
One of the hallmarks of sex education traditionally has been its Cartesian endorsement of mind/body dualism; we have preferred to equate ‘self’ as synonymous with ‘mind’, and have invested heavily in believing in the valence of rationality‐based sexualities education. We generally do not consider the way ‘self’ negotiates, interprets and relates to sexual knowledge in all of our complexity, including our messy, embodied and emotional lives. In this paper I address what I think are several much‐needed conversations for a holistic pedagogy of sexualities to incorporate, including the falseness of the mind/body split, reconsidering what counts as sexual knowledge, the role of the performative in communicating our sexual knowing, and the importance of considering affect in learning about sexualities. The second part of the paper examines pedagogical considerations currently absent in dialogues of sexualities education, such as incorporating transformational learning strategies in teaching sexualities, and what it means to educate toward being a sexual citizen. Finally, I will outline how discussions of epistephenomenology (our relationship to and how we experience knowledge) can contribute to moving toward a vision of a critical, cultural sexualities education.
Number: 1
Keywords: approches et analyses; corps; discipline; discours dominant; phénoménologie; ressource en ligne; savoir expérientiel; science de l'éducation; sciences humaines; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; émotions; épistémologie

Voiles racialisés : la femme musulmane dans les imaginaires occidentaux - Al-Saji, Alia (Les ateliers de l'éthique, 2008)
Cet article étudie deux contextes français dans lesquels les voiles musulmans sont devenus hypervisibles : le débat public qui a mené à la loi française de 2004 interdisant les signes religieux ostensibles dans les écoles publiques, et le projet colonial français de dévoiler les femmes algériennes. Je montre comment le concept de « l’oppression de genre » s’est naturalisé au voile musulman d’une telle manière qu’il justifie les normes de féminités occidentales et cache le mécanisme par lequel les femmes musulmanes sont racialisées. C’est ainsi que le voile devient le point de mire d’un racisme culturel qui se présente comme libérant les femmes musulmanes, un racisme qui semble poser un dilemme au féminisme
Keywords: approches et analyses; corps; cours; discipline; droits des femmes*; europe; fem3400; femmes* musulmanes; france; histoire et politique; phi4336; philosophie; premier cycle; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques

Le droit à l’avortement, une lutte exemplaire - Revue À bâbord ! - bâbord!, Revue À (2008)
Militante de longue date pour le droit à l’avortement, Louise Desmarais publie en 1998 La lutte pour le droit à l’avortement, histoire d’une bataille inachevée. Elle présente ici les principales caractéristiques et les moments forts, selon elle, de la lutte pour le droit à l’avortement au Québec.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amériques; approches et analyses; avortement; canada; care; corps; cours; discipline; histoire; justice reproductive; justice sociale; militance; pol4102; premier cycle; périodes historiques; québec; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social

Émergence et activités de l’organisation internationale des intersexué·e·s - Guillot, Vincent (Nouvelles Questions Feministes, 2008)
Number: 1 Publisher: Éditions Antipodes
Keywords: 1900-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; europe; histoire et politique; hétérosexisme; identités LGBTQIA2+; militance; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Décoloniser les représentations: esquisse d'une géographie culturelle de nos « Autres » - Hancock, Claire (Annales de géographie, 2008)
Cet article propose d’appliquer les méthodes et axes de réflexion de la géographie culturelle (analyse des discours et représentations, attention à la formation discursive d’identités socio-spatiales) à certains des enjeux de notre société post-coloniale, et notamment aux identités et territorialités contraintes qu’elle octroie aux populations dites « issues de l’immigration ». Il suggère également de reposer « au féminin » certaines des interrogations sur ces identités.
Keywords: 2000 à aujourd'hui; approches et analyses; corps; cours; discipline; europe; féminisme décolonial; justice sociale; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; système colonial; systèmes d'oppressions; thématiques; violences

Intersex: a perilous difference - Holmes, Morgan (Susquehanna University Press, 2008)
As threatening evidence that sex is not the natural basis upon which oppositional gender roles are built, the intersexed are made to disappear into normative categories, thus aligning once again the rightful place of male and female as opposites.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; patriarcat; personnes intersexes; premier cycle; santé; sciences humaines; soc2014; sociologie; système médical; systèmes d'oppressions; thématiques; violences; violences médicales

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Breaking the taboo: An exploration of female university students' experiences of attending a feminist‐informed sex education course - Askew, Julie (Sex Education : Sexuality, Society and Learning, 2007)
This article presents the results of a qualitative interview study of nine young women who attended a feminist-informed human sexuality course as undergraduate students at a US university located in the "Bible belt". The course focused on messages of desire and empowerment, rather than romance or fear, and was designed to encourage students to think critically about current sexual discourses. Results indicate that participants' information on sexual issues prior to taking the course was limited and largely negative. Experiences of the course are described in themes including owning sexual desire, improved body image, reduced guilt and fear, and increased confidence as a woman. It is concluded that sex education may be used to help empower female students and enrich their quality of life; current educational practices should therefore be examined for ways in which they are oppressive to development.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; discipline; image corporelle; jeunes femmes*; pédagogie; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle; états-unis; étude qualitative

Le contrôle social réservé aux femmes: entre prison, justice et travail social - Cardi, Coline (Déviance et Société, 2007)
Très peu d’études sociologiques françaises ont tenté une approche de la déviance en termes de genres: la sous-représentation statistique des femmes dans la sphère pénale suffit souvent à les écarter des analyses. Pourtant, prendre pour objet la déviance des femmes permet d’éclairer le fonctionnement du processus pénal, notamment dans son rapport avec des dispositifs parapénaux qui contribuent à distribuer de façon différentielle la déviance des hommes et celle des femmes. Ainsi, partir de la marge, que représentent les femmes incarcérées, est un moyen d’interroger le centre et de saisir en quoi, s’il faut penser la prison en lien avec l’ordre social, il faut également et conjointement la penser en lien avec l’ordre sexué et les normes qui lui sont liées.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; cours; discipline; europe; france; justice sociale; premier cycle; prison; périodes historiques; régions géographiques; sciences humaines; thématiques; travail social; trs1205; violences

The affective turn: Theorizing the social - Clough, Patricia Ticineto; Halley, Jean (Duke University Press, 2007)
In the mid-1990s, scholars turned their attention toward the ways that ongoing political, economic, and cultural transformations were changing the realm of the social, specifically that aspect of it described by the notion of affect: pre-individual bodily forces, linked to autonomic responses, which augment or diminish a body’s capacity to act or engage with others. This “affective turn” and the new configurations of bodies, technology, and matter that it reveals, is the subject of this collection of essays. Scholars based in sociology, cultural studies, science studies, and women’s studies illuminate the movement in thought from a psychoanalytically informed criticism of subject identity, representation, and trauma to an engagement with information and affect; from a privileging of the organic body to an exploration of nonorganic life; and from the presumption of equilibrium-seeking closed systems to an engagement with the complexity of open systems under far-from-equilibrium conditions. Taken together, these essays suggest that attending to the affective turn is necessary to theorizing the social.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; corps; discipline; identités; périodes historiques; représentations; sciences humaines; sciences sociales; sociologie; thématiques; traumatismes; émotions

Les clôtures symboliques des Algériennes: la virginité ou l'honneur social en question - FERHATI, Barkahoum (Clio. Femmes, Genre, Histoire, 2007)
Liée à l'honneur de la famille, la virginité est une question qui a toujours hanté l'esprit des jeunes filles algériennes. Toutes sortes de pratiques sont envisagées par la société pour la préserver. La plus connue est celles du rbat (action de nouer), dit teskar (action de fermer) ou encore tesfah (action de blinder). Au moyen de techniques ritualisées, elle consiste en la « fermeture » symbolique de l'hymen avant la puberté et son « ouverture » symbolique la veille du mariage. La « chemise tachée du sang de la vierge » doit en être la preuve indéniable: elle authentifie que l'honneur de la famille, du groupe, est intact. Lorsque, pour diverses raisons, l'hymen fait défaut, la société déploie toutes sortes de stratégies palliatives. Aujourd'hui, le certificat de virginité et la reconstitution de l'hymen par la chirurgie plastique, l'hyménorrapie ou l'hyménoplastie, viennent renforcer la pratique symbolique du rabt. La question fondamentale que je pose dans cet article est: peut-on envisager de casser la clôture « malléable » de cette « vaste prison » des femmes afin que les Algériennes puissent intégrer la société en tant qu'individus et non en tant qu'emblèmes de l'honneur de la famille?
Keywords: afrique; algérie; anthropologie; approches et analyses; corps; cours; discipline; féminisme islamique; histoire; hymen; patriarcat; premier cycle; rapports sociaux de sexe; ressource en ligne; rituel; régions géographiques; sciences humaines; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; virginité

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

‘Psy’, ‘coach’ et travail dans ‘l'entreprise du couple’: les femmes en première ligne dans Actes du 4e Congrès international des recherches féministes dans la francophonie plurielle - Jonas, Irène (Actes du 4e Congrès international des recherches féministes dans la francophonie plurielle, 2007)
Avec les revendications féministes, la famille a connu de nombreuses et profondes transformations au cours de ces dernières années. Elles ont pourtant été inégalement réalisées et, lorsqu’elles le furent, elles n’ont pas pour autant aplani toutes les difficultés. Ces textes traitent de l’accouchement, de l’avortement, de la contraception, du divorce, du mariage et de la recomposition familiale, des relations de couple, aux quatre coins de la francophonie: le Brésil, la France, la Grèce, le Sénégal, la Suisse et le Québec. Situations forcément différentes et pourtant questions communes susceptibles d’élargir la réflexion transfrontalière face à une institution, la famille, partout remise en cause, avec les premiers balbutiements de l’égalité des sexes. Textes de Fatou Binetou Dial, Nikoletta Chardalia, Irène Jonas, Françoise Le Borgne-Uguen, Ana Liesi Thurler, Sylvie Perrier, Éliane Perrin et son équipe, Isabelle Puech, Catherine Pugeault-Cicchelli, Lucia Scavone, Carmen Susana Tornquist, Hélène Trellu et une introduction de Marie-Blanche Tahon.
Section: 3 volumes : illustrations ; 23 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; brésil; care; corps; cours; discipline; france; francophonie; grèce; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; suisse; sénégal; thématiques; travail; travail social; trs1205

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Les tactiques féministes confrontées aux « tirs amis » dans le mouvement des femmes en Irlande - Taylor, Judith (Politix, 2007)
Cet article examine les modèles courants d’intelligibilité de l’interaction tactique entre les acteurs des mouvements sociaux et montre leur insuffisance pour rendre compte de l’invention tactique dont a dû faire preuve le mouvement des femmes en Irlande. Une analyse des efforts déployés par les féministes irlandaises pour l’extension du droit à l’avortement met en question l’idée que les innovations tactiques ne répondraient qu’aux contre-mouvements ou à la répression de l’État. L’expression « tir ami » fait référence au processus par lequel des groupes qui ne sont pas en opposition avec un mouvement, mais qui n’en font pas non plus partie, constituent une menace pour les finalités de ce mouvement. L’observation de la campagne féministe, de ses meetings et de l’ensemble de sa mise en scène politique donne des aperçus significatifs sur les effets des tirs amis et, spécifiquement, sur le rôle des hommes dans les mouvements de femmes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; avortement; care; corps; cours; discipline; droits des femmes*; europe; intersectionnalité; irlande; justice reproductive; justice sociale; pol5185; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques

Female Sexual Dysfunction: A Case Study of Disease Mongering and Activist Resistance - Tiefer, Leonore (PLoS Medicine, 2006)
"Tiefer highlights key steps in the ""creation"" of a new diagnosis, female sexual dysfunction, and of the campaign to challenge its reductionist approach to women's sexual problems. "
Number: 4
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; inégalités; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." – Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Governing women's morality: a study of Islamic veiling in Canada - Atasoy, Y. (EUROPEAN JOURNAL OF CULTURAL STUDIES, 2006)
The veiling of Muslim women is subject to strongly contested ideas about whether the veil is a symbol of women's subordination to an oppressive tradition or a means of emancipation from that tradition. This article suggests that women's own personal reasons for veiling must be analysed. Data collected from published documents from Muslim organizations allows for demonstration that the veil is configured as central to an Islamic moral code of female modesty. A further analysis of findings from interviews conducted with veiled Muslim women in Winnipeg shows the nuanced ways in which women enact this code.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; corps; cours; discipline; féminisme islamique; histoire et politique; identité; manitoba; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; winnipeg

Queering the Binaries: Transsituated Identities, Bodies, and Sexualities - Cromwell, Jason (The transgender studies reader, 2006)
Keywords: 1900-1999; approches et analyses; corps; cours; discipline; fem1000; histoire; identités LGBTQIA2+; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; thématiques; états-unis

The Cyborg Embryo: Our Path to Transbiology - Franklin, S. (THEORY CULTURE AND SOCIETY, 2006)
It is useful on the occasion of the 21st anniversary of the ‘Cyborg Manifesto’ not only to reconsider its lessons in the context of what is frequently described as the re-engineering of ‘life itself’, but to look at Haraway’s earlier work on embryos. In this article I begin with Haraway’s analysis of embryology in the 1970s to suggest her cyborg embryo was already there, and has, if anything, gained relevance in today’s embryo-strewn society. I argue further, as the title suggests, that the cyborg embryo has been crucial in defining our path to what I am calling here, building on Haraway’s notion of trans from Modest_Witness, ‘transbiology’ - broadly meaning stem cell research, cloning, tissue engineering and regenerative medicine. To illustrate this argument I draw on recent ethnographic fieldwork in a new stem cell derivation facility in the UK built adjacent to an IVF surgery. Using this example, I explore the important and paradoxical role of IVF in the emergence of stem cell science, cloning and transbiology, suggesting that Haraway’s analysis remains crucial to understanding the ironic and contradictory, and unexpectedly generative, circumstances through which the IVF-stem cell interface - the door to transbiology - came into being.
Keywords: approches et analyses; biologie; care; corps; cours; discipline; discours dominant; fecondation in vitro; féminisme cyborg; justice reproductive; lit4700; maternité; premier cycle; ressource en ligne; santé; sciences; sciences humaines; sociologie; systèmes d'oppressions; thématiques

S’approprier son corps et sa santé. Entretien avec Rina Nissim - Fussinger, Catherine; Rey, Séverine; Vuille, Marilène (Nouvelles Questions Feministes, 2006)
Parmi les personnes qui ont réellement fait avancer les choses et apporté des changements dans la vie de beaucoup de femmes, il y a Rina Nissim qui a oeuvré depuis son engagement au sein du MLF de Genève au début des années 1970 pour que les femmes se réapproprient leur corps et leur santé. Ce numéro de « Nouvelles Questions féministes » sur la santé consacre une bonne partie de ses pages à une discussion avec Rina Nissim. Cette militante du groupe « avortement » et self-help » du MLF genevois raconte comment elle est passée de l'école d'infirmière à une vie de militantisme et de voyages, avec la naturopathie pour bagage. Publiant des ouvrages sur la santé des femmes ayant eu un succès important tel que « Mamamélis », cette pionnière en Suisse ouvre le « dispensaire des femmes »fonctionnant sur un mode autogéré, suite à un voyage aux États-Unis, avec d'autres femmes infirmières psychologues et médecins. Les femmes vont alors trouver une alternative aux rapports de pouvoirs classiques des relations médecin-patient et aux médicaments traditionnels, dans un mouvement de prise de conscience et d'action sur leur propre corps. L'engagement international de Rina, en Amérique Central et en Inde principalement où elle s'installe cinq ans et coordonne différents projets, aura permis a de nombreuses femmes de se découvrir elles-mêmes et les autres, de se débarrasser de la honte et se rendre compte que la maladie est souvent liée à un positionnement social.
Number: 2 Publisher: Éditions Antipodes
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique centrale; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; europe; france; inde; justice reproductive; premier cycle; périodes historiques; racisme; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; suisse; systèmes d'oppressions; thématiques; travail; états-unis

Les sciences et la construction des identités sexuées. Une revue critique - Gardey, Delphine (Annales. Histoire, Sciences Sociales, 2006)
Cet article rend compte des travaux en sciences sociales qui se sont intéressés aux sciences et à leur rôle dans la construction des identités sexuées. Il poursuit trois objectifs : introduire à une réflexion sur ce qu’a été dans le passé le savoir sur la différence des sexes et sur ce qui constitue dans différents corpus de connaissances scientifiques le féminin et le masculin, les femmes et les hommes ; repousser au plus loin les frontières communément admises de la naturalité du corps féminin, interroger le « fait » ou le « donné » du sexe – d’autres diraient la matérialité et la discursivité du sexe ; insister sur les façons dont les sciences contemporaines se mêlent et s’emmêlent dans la construction des identités sexuées, en focalisant l’attention sur les travaux qui montrent comment les sciences et les techniques transforment littéralement les corps. Il n’est alors plus seulement question de fabrication des sexes et du genre, mais de redéfinition des frontières et des limites des corps. Au-delà de la contribution historienne à ces réflexions, l’article met en évidence l’affirmation d’un champ de recherche à l’intersection des études de genre et des études sociales des sciences et des techniques qui emprunte à des traditions disciplinaires et méthodologiques et définit de nouveaux objets et de nouvelles manières de faire les sciences sociales.
Number: 3
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; essentialisme; europe; france; féminisme radical; histoire et politique; identités LGBTQIA2+; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail

La sexualité entre sexisme et racisme: les descendantes de migrant·e·s du Maghreb et la virginité - Hamel, Christelle (Nouvelles Questions Féministes, 2006)
L'article présente le résultat d'une recherche sur la vie affective et sexuelle des jeunes Français-es descendant de migrant-e-s originaires du Maghreb, qui décrit comment les jeunes femmes se positionnent par rapport au principe de virginité. Alors que cette norme est un mode de contrôle de la sexualité des femmes, certaines le revendiquent, tandis que celles qui l'ont transgressé expriment combien cette décision leur fut difficile. Pour comprendre la prégnance de leur attachement à la valeur de la virginité, l'autrice replace leurs discours et pratiques dans le contexte social qui les a fait naître. Elle décrit donc comment les discriminations et la stigmatisation racistes façonnent l'expérience de vie de ces jeunes femmes et montre combien cette expérience du racisme se combine à l'expérience du sexisme dans les familles et dans la société globale. Ici, l'imbrication du sexisme et du racisme fait peser sur elles un système de contraintes complexe qui les soumet à des injonctions paradoxales. Ce n'est qu'au regard de ces injonctions que la revendication par certaines de cette norme qui par ailleurs les opprime devient intelligible.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; corps; cours; discipline; europe; france; histoire et politique; intersectionnalité; maghreb; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; virginité; études démographiques

Médicalisation de la ménopause, mouvements pour la santé des femmes et controverses sur les thérapies hormonales - Löwy, Ilana; Gaudillière, Jean-Paul (Nouvelles Questions Feministes, 2006)
Le traitement hormonal de la ménopause, présenté entre 1970 et 2000 par la majorité des experts comme capable d’accroître le bien-être des femmes mais aussi de prévenir des nombreuses pathologies liées au vieillissement féminin, a été déclaré en 2002 inutile et dangereux suivant un essai clinique nord américain, Women’s Health Initiative (WHI). En voie de conséquence, les prescriptions de ce traitement ont chuté dramatiquement entre 2002 et 2005. Cet article retrace les origines féministes de WHI, puis suit les conséquences de la publication de ses résultats aux États-Unis, en France et en Allemagne. En conclusion, il revient sur les tensions entre les rôles des femmes comme utilisatrices des hormones, comme expertes et comme militantes des mouvements pour la santé des femmes.
Number: 2 Publisher: Éditions Antipodes
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; allemagne; amérique du nord; amériques; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Les représentations de la féminité et de la masculinité à travers le thème des rapports amoureux dans la chanson populaire francophone consommée au Québec, 1960-1990 - Ouellette, Myrthô (Université de Sherbrooke, 2006)
Les cinq chansons francophones en tête des palmarès radio et de ventes québécois pour la période comprise entre 1960 et 1990 ont en très forte majorité pour thème central l'amour. Or, comme le souligne Geneviève Sellier à propos du cinéma,"le privilège accordé aux"histoires d'amour" rend nécessaire l'utilisation des théorisations concernant les rapports sociaux de sexe" 1. Ainsi, étudier à la lumière de la notion de genre les paroles des chansons les plus consommées annuellement s'impose. Cette analyse est d'autant plus nécessaire que ces trois décennies ont été marquées par la libération sexuelle et les mouvements féministes, éléments annonciateurs de bouleversements des identités sexuées. Nous tenterons d'évaluer comment, à travers le thème des rapports amoureux, la chanson populaire francophone consommée au Québec représente les identités sexuées entre 1960 et 1990. Nous constaterons que le thème des rapports amoureux s'est fortement modifié au cours de la période. On assiste au déclin du"mythe du Prince Charmant". Toutefois, l'hétéronormativité, loin d'être remise en question dans les chansons, tend à être accentuée au cours de la période. Si au niveau des rapports amoureux, la chanson populaire reflète certains bouleversements en cours dans la société québécoise, elle est loin de remettre en question les catégories homme-femme. L'érosion du mythe de l'amour n'a pas permis de mettre fin à la bicatégorisation dans la chanson, malgré une plus grande souplesse des représentations des identités sexuées. 1 Geneviève Sellier,"Une histoire du cinéman avec les femmes est-elle possible?", dans Anne-Marie Sohn et Françoise Thélamon dir., L'histoire sans les femmes est-elle possible ?, [S. I.] Perrin, 1998, p. 143.
http://savoirs.usherbrooke.ca/handle/11143/2460
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amour; amériques; analyse de discours; approches et analyses; corps; culture populaire; discipline; histoire; hétérosexisme; mémoires/thèses; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques

The Politics of Protection: Body Image, Social Pressures, and the Misrepresentation of Young Black Women - Poran, Maya A. (Sex Roles : A Journal of Research, 2006)
As part of a larger multi-method study, 15 Black women college students participated in focus group discussions on the body. Contrary to popular theories that propose that Black women are protected by a “Black Culture” that buffers them from negative effects of body representations—thereby leaving them with higher body esteem—the themes that emerged in the focus group discussions indicate that young Black women are indeed feeling (1) pressures to be thin, (2) pressures from the preferences of men of diverse ethnicities, (3) competition with other Black women in the realms of beauty, and (4) a strong sense of being misrepresented by media images of thin Black women. These results not only indicate that body image issues are of real pressing concern to young Black women, but that psychological research methodologies may be adding to the misrepresentation of young Black women and their struggles. Qualitative methods must be utilized in order to hear more clearly the voices of Women of Color.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; image corporelle; intersectionnalité; new york; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; états-unis

Femmes et immigrées: corvéables à merci - Puech, Isabelle (Travail, genre et sociétés, 2006)
Dans le secteur des services, des milliers de femmes connaissent des formes d’exploitation salariale diffuses, peu visibles, socialement tolérées. Cet article propose de mettre en lumière un mode de gestion de la main-d’œuvre non qualifiée qui, sous couvert de flexibilité et de compression maximale des coûts, utilise les femmes les plus vulnérables sur le marché du travail – en particulier les femmes immigrées – comme variable d’ajustement. À partir d’une enquête de terrain menée auprès d’une population de femmes de chambre, l’article s’attachera à mettre au jour une face cachée des emplois précaires. Des emplois souvent à durée indéterminée qui ne protègent pas des conditions de travail pénibles, des temps de travail à rallonge, des salaires au rabais et des pratiques patronales frauduleuses.
Keywords: 1900-1999; 1970-1979; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; afrique subsaharienne; approches et analyses; capitalisme racial; corps; cours; discipline; europe; france; inégalités; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; travail

La santé est politique - Vuille, Marilène; Rey, Séverine; Fussinger, Catherine; Cresson, Geneviève (Nouvelles Questions Feministes, 2006)
Number: 2 Publisher: Éditions Antipodes
Keywords: 1900-1909; 1900-1999; 1970-1979; 1980-1989; 1990-1999; allemagne; approches et analyses; care; corps; cours; discipline; europe; france; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; soc2051; sociologie; suisse; systèmes d'oppressions; thématiques; travail

La chirurgie mammaire et l'esthétiquement correct : le sein et les médias - Le Louarn, S.; Le Louarn, C. (Annales de Chirurgie Plastique Esthétique, 2005)
Résumé Cet article discute en quoi les normes du sein esthétiquement correct, les caractéristiques physiologiques du sein, l'allongement de la durée de vie et les possibilités de la chirurgie esthétique influencent la demande de modification mammaire. Puis il examine comment le sujet des modifications mammaires est traité dans différents médias : presse écrite (notamment féminine), documentaires et spectacles de téléréalité. Il constate un paradoxe entre d'une part, un contexte social qui durcit des normes, encourage la quête du bien-être et la réalisation de soi et prône la tolérance et, d'autre part, la réalité d'un certain déni du droit des femmes à choisir leur apparence mammaire. L'article tente de décrypter les obstacles historiques, philosophiques, sociaux, religieux et idéologiques impliqués. Enfin, il propose une nouvelle grille de lecture du positionnement d'un individu par rapport à la chirurgie esthétique selon deux axes : le « Faire » et le « Dire ». Cette grille pourra aider le chirurgien plasticien à mieux décoder la demande de chaque patiente, pour mieux la satisfaire.
Number: 5
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; corps féminin; cours; discipline; discours médiatique; esthétique; europe; france; féminisme pop; hétérosexisme; occident; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

Un âge critique. La ménopause sous le regard des médecins des XVIIIe et XIXe siècles - Tillier, Annick (Clio. Femmes, Genre, Histoire, 2005)
Si l’on possède peu de témoignages sur la manière dont les femmes du XIXe siècle ont vécu le vieillissement, les discours des médecins sur cette question abondent. La ménopause est décrite par eux comme une période particulièrement dangereuse qui, à l’instar de la puberté, bouleverse toute l’économie de la femme. Au nombre des maladies qui sont susceptibles de l’assaillir lorsque s’interrompt le mécanisme régulateur que représentait la menstruation s’ajoute la blessure narcissique que provoque la perte de sa féminité et l’entrée dans l’âge de décrépitude. Plus encore, la femme perdant avec la faculté d’engendrer sa vocation sociale (la maternité), cette période, souvent qualifiée d’âge critique ou d’âge dangereux, s’annonce comme une véritable mort sociale. Privée de sa capacité de séduction, fragilisée par la révolution physiologique qui s’opère en elle, la femme, encouragée à se retirer d’un monde où elle ne peut plus briller, est plus que jamais assignée à la sphère privée.
ISBN: 9782858167814 Number: 21 Publisher: Éditions Belin
Keywords: 1800-1899; 1900-1999; angleterre; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; inégalités; justice reproductive; maternité; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Histoires d’objets - Fassa, Farinaz; Kraus, Cynthia; Malbois, Fabienne (Nouvelles Questions Feministes, 2005)
Number: 1 Publisher: Éditions Antipodes
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; cours; discipline; europe; france; féminisme radical; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Black sexual politics: African Americans, gender, and the new racism - Hill Collins, Patricia (Routledge, 2005)
To a large extent, scholarship on black politics often focuses primarily on institutions, rule of law, processes, political actors, and citizens but with very little attention to issues of gender and sexuality. In contrast, the principal aim of this book is to explore what the author sees as the inextricable links between racism and gender. The basic thesis of this well-written, important, and provocative book is that the fight against racism, especially the “new racism,” can never be won without first challenging sexism, which simultaneously oppresses African-American men and women.
Section: ix, 374 p. ; 23 cm
Keywords: afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminismes noirs; intersectionnalité; premier cycle; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; théorie critique de la race; violences; états-unis

Attitudes Toward Victims of Rape: Effects of Gender, Race, Religion, and Social Class - Nagel, Barbara; Matsuo, Hisako; McIntyre, Kevin P.; Morrison, Nancy (Journal of Interpersonal Violence, 2005)
Although previous literature focusing on perceptions of victims of rape has examined how gender, race, and culture influence the attitudes one holds toward victims, these studies have yielded mixed results. This study compared perceptions of victims of rape across a wide range of ages, educational backgrounds, religions, and income levels, while focusing on gender and racial differences. Results indicate (N = 220) that victims of rape are generally viewed more sympathetically by females than by males and by Whites than by African Americans. However, the effect of race disappears when socioeconomic variables are controlled, suggesting a more complex relationship. Also, a hierarchical regression indicates that age, sex, education, and income are significant predictors of attitudes toward victims. This study builds on existing research that examines such attitudes from a cultural perspective and extends this literature by examining the interactive effects of several demographic variables within a community sample.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Domestic violence at the intersections of race, class, and gender: challenges and contributions to understanding violence against marginalized women in diverse communities - Sokoloff, Natalie J; Dupont, Ida (Violence against women, 2005)
This article provides a comprehensive review of the emerging domestic violence literature using a race, class, gender, sexual orientation intersectional analysis and structural framework fostered by women of color and their allies to understand the experiences and contexts of domestic violence for marginalized women in U.S. society. The first half of the article lays out a series of challenges that an intersectional analysis grounded in a structural framework provides for understanding the role of culture in domestic violence. The second half of the article points to major contributions of such an approach to feminist methods and practices in working with battered women on the margins of society.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; care; corps; cours; criminologie; discipline; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; violences; états-unis

Cerveau, sexe et pouvoir - Vidal, Catherine; Benoit-Browaeys, Dorothée. (Belin, 2005)
À la lumière des connaissances actuelles en neurosciences, on serait tenté de croire que les vieux préjugés sur les différences biologiques entre les hommes et les femmes ont été balayés. Ce n'est manifestement pas le cas : médias et ouvrages de vulgarisation prétendent que les femmes sont " naturellement " bavardes et incapables de lire une carte routière, tandis que les hommes sont nés bons en maths et compétitifs. Ces discours laissent croire que nos aptitudes, nos émotions, nos valeurs sont tablées dans des structures mentales immuables depuis les temps préhistoriques. Cet ouvrage, qui s'adresse à un large public, replace le débat autour de la différence des sexes sur un terrain scientifique rigoureux, au-delà des idées reçues. L'enjeu est de comprendre le rôle de la biologie, mais aussi l'influence de l'environnement social et culturel dans la construction de nos identités d'hommes et de femmes. Notre destin n'est pas inscrit dans notre cerveau! [Source : d'après la 4e de couv.].
Keywords: 2000 à aujourd'hui; approches et analyses; corps; cours; discipline; discours dominant; inégalités; neuropsychologie; neurosciences; premier cycle; psy4910; psychologie; périodes historiques; sciences; sciences humaines; sexe/genre; sexisme; systèmes d'oppressions; thématiques

« Une ‘mauvaise mère’ nommée Québec » dans Un Québec en mal d'enfants: la médicalisation de la maternité, 1910-1970 - Baillargeon, Denyse (Un Québec en mal d'enfants: la médicalisation de la maternité, 1910-1970, 2004)
Comment les médecins sont-ils parvenus à convaincre les femmes de la nécessité de les consulter, non seulement au moment de l’accouchement mais aussi durant la grossesse et, par la suite, durant la première année de leur enfant? Pourquoi et à quelles conditions celles-ci ont-elles choisi de suivre leurs prescriptions? Denyse Baillargeon répond à ces questions en s’attardant aux différents aspects du processus de médicalisation de la maternité entre les années 1910 et 1970. Son analyse s’intéresse au discours des médecins canadiens-français à l’égard de la mortalité infantile et de la maternité et au développement des services médicaux mis gratuitement à la disposition des mères durant cette période. Fondé sur une vaste recherche documentaire, et sur une soixantaine d’entrevues avec des femmes, cet ouvrage fait ressortir la multiplicité des acteurs sociaux qui ont pris part à ce processus et souligne les alliances, les conflits et les jeux de pouvoir qui les ont rassemblés ou opposés, pour révéler toute la complexité d’un phénomène qui a profondément transformé la maternité et la société québécoise.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; droit des femmes*; famille; his4523; histoire; justice reproductive; justice sociale; maternité; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Precarious life: The powers of mourning and violence - Butler, Judith (Verso, 2004)
Responding to the US’s perpetual war, Butler explores how mourning could inspire solidarity.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; discipline; guerre; histoire et politique; médias; philosophie; périodes historiques; régions géographiques; sciences humaines; thématiques; violences; états-unis; éthique

Dictionnaire critique du féminisme - Hirata, Helena (Presses universitaires de France, 2004)
Avortement et contraception, citoyenneté, division sexuelle du travail et rapports sociaux de sexe, domination, famille, féminité-masculinité-virilité, harcèlement sexuel, histoire (sexuation de l'), maternité, migration, mixité, mondialisation, mouvements féministes, parité , patriarcat (théories du), précarisation sociale, prostitution, sexualité, transmissions intergénérationnelles, syndicats, travail domestique, violences.dictionnaire est de changer la façon commune de penser " : l'ambition de Diderot est reprise avec force par les auteurs de ce parcours historique etcritique duféminisme . Cette volonté éditoriale s'exprime dans le choix typologique des entrées : des concepts nouveaux issus de la théorisation féministe, des champs d'intervention des luttes féministes, des notions transversales d'économie et de sociologie du travail.Dictionnaire théorique et politique, pluriel et engagé, cet ouvrage se veut aussi un texte de conviction et d'explication.
Keywords: 1900-1999; approches et analyses; avortement; corps; cours; cycles supérieurs; dictionnaire critique; discipline; europe; fem1000; fem7000; france; har4600; histoire et politique; interdisciplinarité; justice reproductive; lit2815; lit3220; lit3495; militance; outils; ouvrages de références; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sexualité; sociologie; thématiques; travail

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Rowman & Littlefield, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Section: x, 193 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

Unbearable weight: Feminism, western culture, and the body - Bordo, Susan (University of California Press, 2003)
Susan Bordo untangles the myths, ideologies, and pathologies of the modern female body. Bordo explores our tortured fascination with food, hunger, desire, and control, and its effects on women's lives
Keywords: 2000 à aujourd'hui; 2000-2009; corps; cours; discipline; fem1000; image corporelle; occident; philosophie; premier cycle; périodes historiques; sciences humaines; thématiques; études culturelles

Handicap, recherche et changement social. L’émergence du paradigme émancipatoire dans l’étude de l’exclusion sociale des personnes handicapées - Boucher, Normand (Lien social et Politiques, 2003)
Le champ du handicap a subi de profondes transformations au cours des quatre dernières décennies dans la majorité des sociétés postindustrielles. Ce phénomène, qui influence les approches théoriques et la recherche à l’intérieur des sciences sociales, a fait surgir un nouveau paradigme émancipatoire basé sur une remise en cause des rapports entre le chercheur et le « sujet d’étude ». Dans cet article, nous explorons le développement de ce paradigme en nous appuyant sur l’expérience britannique, et nous discutons de son apport à la compréhension du handicap et des politiques sociales en abordant la question du rôle et de la position des acteurs au sein de la pratique de recherche
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; EDI; approches et analyses; capacitisme; corps; cours; discipline; histoire et politique; premier cycle; périodes historiques; ressource en ligne; ré; santé; sciences humaines; sex1920; sociologie; systèmes d'oppressions; thématiques; études critiques du handicap

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Le corps sens dessus dessous: regards des sciences sociales sur le corps - Ciosi-Houcke, Laure; Pierre, Magali (L'Harmattan, 2003)
Corps musclé, silhouette affinée, organes percés, membres tatoués, le corps se travaille, s'affiche, s'exprime. Dans les sociétés occidentales contemporaines, les individus entendent le cultiver, le transformer, le dompter et le dressent comme un emblème. Le présent ouvrage fait non seulement le point sur "la sociologie des pratiques corporelles", mais rend compte, à travers différents articles, du rôle des représentations et des pratiques du corps dans les interactions et les catégorisations sociales.
Section: 208 pages ; 22 cm
Keywords: corps; cours; discipline; lit4700; premier cycle; sciences humaines; sociologie; thématiques

La fabrique moléculaire du genre : hormones sexuelles, industrie et médecine avant la pilule - Gaudillière, Jean-Paul (Cahiers du Genre, 2003)
L’histoire des hormones sexuelles est le plus souvent discutée en référence à l’invention de la pilule dans les années d’après-guerre. La molécularisation des sexes a toutefois été beaucoup plus précoce, plus complexe et plus contradictoire que cette vision ne le laisse penser. Parce qu’elle a fait intervenir tout à la fois une recherche biomédicale de haut niveau, une industrie pharmaceutique puissante et la biopolitique du régime nazi, la configuration allemande offre un terrain privilégié pour interroger les dynamiques de cette fabrique moléculaire du genre. Centré sur les rapports entre biologistes, industriels producteurs d’hormones et médecins spécialistes de la reproduction, cet article aborde trois aspects différents de l’histoire des stéroïdes sexuels avant la pilule : l’idée d’un continuum des sexes biologiques et les discussions qu’elle a suscitées, la médicalisation de la stérilité féminine et de la ménopause, et les multiples usages de la testostérone.
Number: 1 Publisher: L'Harmattan
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; féminisme radical; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Travailler à l'élimination du trafic sexuel des femmes - Matte, Diane; Kurtzman, Lyne (Canadian Woman Studies, 2003)
Au cours des deux dernieres annees, le mouvement des femmes du Quebec a ete happe par le debat concernant la prostitution et le trafic sexuel. Dans le contexte de l'organisation de la Marche mondiale des femmes, un groupe de Montreal, Stella, regroupant des travailleuses du sexe et qui est membre de la Federation des femmes du Quebec (FFQ) a propose que la Marche quebecoise porte des revendications concernant la decriminalisation de l'industrie du sexe en se basant sur une analyse: qui reconnait la prostitution comme un metier comme un autre; qu'il est utopique de vouloir l'eliminer; que cette lutte serait contre-productive au regard des besoins des femmes prostituees et que la priorite du mouvement des femmes doit etre de mettre fin a la discrimination envers les femmes dans cette industrie. Le debat etait lance et n'a pu etre resolu autour des revendications quebecoises de la Marche mondiale des femmes. Les femmes du Quebec ont tout de meme defendu des revendications reconnaissantl'importance de mettre fin a la discrimination dont sont victimes les prostituees dans le systeme judiciaire et les services sociaux et denoncant la violence et les abus dont elles sont victimes. Par rapport a ces grandes lignes, on peut affirmer qu'il y a consensus.
Keywords: amériques; approches et analyses; canada; communication; corps; cours; discipline; justice sociale; premier cycle; prostitution; québec; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; sociologie; thématiques; travail; violences

Le sexe des hormones : l'ambivalence fondatrice des hormones sexuelles - Sinding, Christiane (Cahiers du Genre, 2003)
Les hormones sexuelles ont été inventées à la fin du XIXe siècle comme un élixir de vie d’origine masculine. Mais ce sont les effets thérapeutiques d’autres hormones qui validèrent aux yeux de la communauté scientifique l’existence de ces nouvelles molécules. Obéissant au modèle culturel dominant de l’existence de deux sexes bien distincts, les biologistes affirmèrent qu’il existait des hormones « masculines » agissant sur les organes considérés comme masculins, et des hormones « féminines » agissant sur les caractères « féminins ». Quand on s’aperçut que les hormones masculines pouvaient avoir des effets « féminisants » sur certains organes féminins et réciproquement, on préféra mettre en doute le sexe des sujets testés plutôt que de remettre en cause le modèle binaire des sexes. Ce n’est que vers les années 1980 que certaines féministes et minorités sexuelles remirent en question le modèle biologique binaire des sexes. La pilule contraceptive fut inventée comme un outil de « libération des femmes », mais aussi de régulation des taux de naissance destiné aux pays surpeuplés et pauvres. Des hormones sexuelles sont utilisées chez des sujets sains, comme les sportifs, pour améliorer leurs performances physiques. Les hormones furent donc inventées comme agents doubles, destinés à soigner des malades, mais aussi à transformer des sujets sains.
Number: 1 Publisher: L'Harmattan
Keywords: 1900-1999; 1980-1989; 1990-1999; approches et analyses; corps; cours; discipline; discours; discours dominant; europe; france; postmodernisme; premier cycle; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Corps reproducteur et techniques procréatives : images, brouillages, montages et remue-ménage - Tain, Laurence (Cahiers du Genre, 2003)
C’est la fabrication du corps reproducteur dans le contexte actuel des techniques médicales de procréation qui est l’objet de cette contribution. Trois dimensions de cette production du corps, envisagée comme un processus à la fois biologique et social en constant réaménagement, sont abordées successivement ici : l’image dessinée par la recherche scientifique ; l’ancrage dans la standardisation hospitalière ; le montage social découlant des réglementations. L’observation de différents indicateurs du système de genre dans chacun de ces registres — les attributs masculins et féminins, le siège de la reproduction, le système de sexualité — incite à conclure à une reproduction des rapports de genre. Néanmoins, on assiste simultanément à une plasticité corporelle, à un brouillage des catégories impliquant de nouvelles tensions : rien ne paraît donc définitivement joué dans les combinaisons potentielles des rapports sociaux entre hommes, femmes, chercheurs et médecins.
Number: 1 Publisher: L'Harmattan
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; approches et analyses; corps; corps des femmes; cours; discipline; europe; france; maternité; postmodernisme; premier cycle; procréation; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; thématiques

Integrating Disability, Transforming Feminist Theory - Garland-Thomson, Rosemarie (NWSA Journal, 2002)
This essay aims to amplify feminist theory by articulating and fostering feminist disability theory. It names feminist disability studies as an academic field of inquiry, describes work that is already underway, calls for needed study and sets an agenda for future work in feminist disability studies. Feminist disability theory augments the terms and confronts the limits of the ways we understand human diversity, the materiality of the body, multiculturalism, and the social formations that interpret bodily differences. The essay asserts that integrating disability as a category of analysis and a system of representation deepens, expands, and challenges feminist theory. To elaborate on these premises, the essay discusses four fundamental and interpenetrating domains of feminist theory: representation, the body, identity, and activism, suggesting some critical inquiries that considering disability can generate within these theoretical arenas.
Keywords: EDI; activisme; approches et analyses; corps; cours; discipline; militance; premier cycle; queer; ressource en ligne; santé; sciences humaines; sciences sociales; sex1920; thématiques; études critiques du handicap; études féministes

The female circumcision controversy: an anthropological perspective - Gruenbaum, Ellen (University of Pennsylvania Press, 2001)
To the Western eye, there is something jarringly incongruous, even shocking, about the image of a six-year-old girl being held down by loving relatives so that her genitals can be cut. Yet two million girls experience this each year. Most Westerners, upon learning of the practice of female circumcision, have responded with outrage; those committed to improving the status of women have gone beyond outrage to action by creating various programs for "eradicating" the practice. But few understand the real life complexities families face in deciding whether to follow the traditional practices or to take the risk of change. InThe Female Circumcision Controversy, Ellen Gruenbaum points out that Western outrage and Western efforts to stop genital mutilation often provoke a strong backlash from people in the countries where the practice is common. She looks at the validity of Western arguments against the practice. In doing so, she explores both outsider and insider perspectives on female circumcision, concentrating particularly on the complex attitudes of the individuals and groups who practice it and on indigenous efforts to end it. Gruenbaum finds that the criticisms of outsiders are frequently simplistic and fail to appreciate the diversity of cultural contexts, the complex meanings, and the conflicting responses to change. Drawing on over five years of fieldwork in Sudan, where the most severe forms of genital surgery are common, Gruenbaum shows that the practices of female circumcision are deeply embedded in Sudanese cultural traditions-in religious, moral, and aesthetic values, and in ideas about class, ethnicity, and gender. Her research illuminates both the resistance to and the acceptance of change. She shows that change is occurring as the result of economic and social developments, the influences of Islamic activists, the work of Sudanese health educators, and the efforts of educated African women. That does not mean that there is no role for outsiders, Gruenbaum asserts, and she offers suggestions for those who wish to help facilitate change. By presenting specific cultural contexts and human experiences with a deep knowledge of the tremendous variation of the practice and meaning of female circumcision, Gruenbaum provides an insightful analysis of the process of changing this complex, highly debated practice.
Section: 242 p. ; 23 cm
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; histoire et politique; justice sociale; point de vue situé; premier cycle; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; soudan; système colonial; systèmes d'oppressions; thématiques; violences

Corps, sexe et art: dimension symbolique - Pearl, Lydie (L'Harmattan, 2001)
Les années 60 marquent le début d'un art éphémère dans lequel l'objet d'art disparaît au profit d'une mise en scène du corps. Les Actionnistes viennois mêlent des corps féminins ou masculins dans la boue, du sang et des organes animaux etc. Comment ce qui peut paraître aberration ou perturbation de la personnalité est souvent une mise en scène microcosmique des idéologies ou des réalités politiques d'une époque : images d'une coupure Est/Ouest, de frontières infranchissables à l'époque de la guerre froide ou, au contraire, effacement des frontières au temps de la mondialisation avec des artistes de la Scène internationales
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; anthropologie; approches et analyses; art contemporain; arts; corps; cours; discipline; har4600; histoire de l'art; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sexualité; thématiques

Marché au sexe - Rubin, Gayle; Butler, Judith P.; Sokol, Eliane (EPEL, 2001)
"Aucun amateur de cuisine épicée ne se verra privé de liberté ou victime d'ostracisme pour avoir satisfait ses papilles gustatives. En revanche, on peut être jeté en prison pour trop aimer les chaussures en cuir. De même, l'homosexualité, le sida, la pornographie, le transsexualisme, et aujourd'hui la pédophilie, donnent-ils lieu à ce que Gayle Rubin appelle une " panique sexuelle ". Chaque panique désigne une minorité sexuelle, généralement inoffensive, comme population-cible. Au terme du processus, celle-ci se trouve décimée, et la société tout entière, juridiquement et socialement, réorganisée. Gayle Rubin a jeté les bases d'un champ autonome d'études sur le sexe où désir, jouissance et diversité érotique, pourraient trouver leur raison théorique et politique. Les trois textes publiés ici s'inscrivent dans une filiation politique (le féminisme, la nouvelle gauche, les luttes antiracistes, les luttes pour les droits civiques) et théorique (les sexologues, Freud, Lacan, Marx, Foucault, Derrida). Les paradigmes ne valent rien sans l'enquête de terrain, et rien non plus s'ils ne s'actualisent en choix de stratégie et de tactique politiques. L'ensemble s'éclaire du partiel, le partiel de l'ensemble. Nous sommes loin ici du communautarisme béat qu'on prête parfois en France aux intellectuels américains. Qu'on lise les critiques acerbes de Judith Butler sur les replis identitaires : les lesbiennes n'ont rien d'autre en commun que leur expérience du sexisme et de l'homophobie. Ou ses réserves sur le coming out : " La sexualité reste-t-elle sexualité quand elle est soumise à un critère de transparence et de révélation? Une quelconque sexualité serait-elle possible sans cette opacité qui a pour nom inconscient? " Gayle Rubin et Judith Butler soulignent constamment la nécessité de ne pas troquer une violence contre une autre, une démonologie religieuse contre une démonologie laïque, laissant ainsi sa chance à l'érotologie moderne. (Éditeur).
Contenue: Entretien : Marché au sexe / Gayle S. Rubin et Judith Butler – Penser le sexe / Gayle S. Rubin – Imitation et insubordination du genre / Judith Butler.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; hétérosexisme; identités LGBTQIA2+; lesbianisme; lit3220; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex3383; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; théories féministes; transféminisme; états-unis

« Penser le sexe: pour une théorie radicale de la politique de la sexualité». Dans Marché au sexe - Rubin, Gayle; Butler, Judith P.; Sokol, Eliane (Marché au sexe, 2001)
Aucun amateur de cuisine épicée ne se verra privé de liberté ou victime d'ostracisme pour avoir satisfait ses papilles gustatives. En revanche, on peut être jeté en prison pour trop aimer les chaussures en cuir. De même, l'homosexualité, le sida, la pornographie, le transsexualisme, et aujourd'hui la pédophilie, donnent-ils lieu à ce que Gayle Rubin appelle une " panique sexuelle ". Chaque panique désigne une minorité sexuelle, généralement inoffensive, comme population-cible. Au terme du processus, celle-ci se trouve décimée, et la société tout entière, juridiquement et socialement, réorganisée. Gayle Rubin a jeté les bases d'un champ autonome d'études sur le sexe où désir, jouissance et diversité érotique, pourraient trouver leur raison théorique et politique. Les trois textes publiés ici s'inscrivent dans une filiation politique (le féminisme, la nouvelle gauche, les luttes antiracistes, les luttes pour les droits civiques) et théorique (les sexologues, Freud, Lacan, Marx, Foucault, Derrida). Les paradigmes ne valent rien sans l'enquête de terrain, et rien non plus s'ils ne s'actualisent en choix de stratégie et de tactique politiques. L'ensemble s'éclaire du partiel, le partiel de l'ensemble. Nous sommes loin ici du communautarisme béat qu'on prête parfois en France aux intellectuels américains. Qu'on lise les critiques acerbes de Judith Butler sur les replis identitaires : les lesbiennes n'ont rien d'autre en commun que leur expérience du sexisme et de l'homophobie. Ou ses réserves sur le coming out : " La sexualité reste-t-elle sexualité quand elle est soumise à un critère de transparence et de révélation? Une quelconque sexualité serait-elle possible sans cette opacité qui a pour nom inconscient? " Gayle Rubin et Judith Butler soulignent constamment la nécessité de ne pas troquer une violence contre une autre, une démonologie religieuse contre une démonologie laïque, laissant ainsi sa chance à l'érotologie moderne.
Section: 175 pages : illustrations ; 21 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; europe; homophobie; hétérosexualité; identités LGBTQIA2+; lesbianisme; occident; phi2030; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; soc2014; thématiques

Les pratiques traditionnelles affectant la santé physique et mentale des femmes; l'excision et l'infibulation - situation actuelle et perspectives d'avenir - Vissandjée, B.; Ndejuru, R.; Kantiébo, M.; Renaud, J.; Aïthachimi, L.; Levine, L.; Lapointe, M. (Institut universitaire SHERPA, 2001)
L’excision et l’infibulation sont parties intégrantes des traditions de nombreuses sociétés africaines issues majoritairement de la région subsaharienne. En contexte canadien, aucune information statistique n’est présentement disponible sur la prédominance de cette pratique, malgré le fait que de nombreux intervenants soupçonnent que plusieurs immigrant(e)s en provenance de ces pays sont susceptibles de faire subir ces pratiques à leurs fillettes. Cette étude qualitative explore les valeurs et les croyances des immigrant(e)s par rapport à ces pratiques traditionnelles, tout en cernant les défis de leur processus d’intégration au Canada et leur recours aux services de santé.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; corps; cours; discipline; interculturalité; migration; médecine; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences; sciences humaines; sciences infirmières; sex2283; sexologie; sexualité; thématiques; violences

Strange encounters: embodied others in post-coloniality - Ahmed, Sara (Routledge, 2000)
"Examining the relationship between strangers, embodiment and community, Strange Encounters challenges the assumptions that the stranger is simply anybody we do not recognize and instead proposes that he or she is socially constructed as somebody we already know. Using feminist and postcolonial theory this book examines the impact of multiculturalism and globalization on embodiment and community whilst considering the ethical and political implication of its critique for post-colonial feminism. A diverse range of texts are analyzed which produce the figure of 'the stranger', showing that it has alternatively been expelled as the origin of danger - such as in neighbourhood watch, or celebrated as the origin of difference - as in multiculturalism. The author argues that both of these standpoints are problematic as they involve 'stranger fetishism'; they assume that the stranger 'has a life of its own'". – Site de l'éditeur.
Keywords: approches et analyses; corps; cours; discipline; féminisme décolonial; histoire et politique; lit4700; philosophie; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; études culturelles

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis

Cahiers du genre: « De la contraception à l’enfantement : l’offre technologique en question » - Béland, Bibiane (Recherches féministes, 2000)
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du sud; approches et analyses; brésil; corps; corps des femmes; cours; discipline; discours dominant; droits des femmes*; europe; france; maternité; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Sexing the body: Gender politics and the construction of sexuality - Fausto-Sterling, Anne (Basic Books, 2000)
Discusses the causes and determining factors of gender behavior differences and sexual identity, particularly biology and societal expectations, and argues that differences between male and female are not always distinct.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme matérialiste; genre; histoire et politique; hétérosexisme; injustices épistémiques; philosophie politique; premier cycle; production des savoirs; ressource en ligne; sciences humaines; sciences sociales; sex3383; sexe/genre; sexualité; sociologie; systèmes d'oppressions; thématiques; épistémologie

L'expérience sociale du quotidien : corps, espace, temps - Haicault, Monique (2000)
Ce livre propose une articulation originale des champs du travail, du privé, des rapports sociaux et de la famille, et constitue une avancée majeure dans le champ de la sociologie des rapports sociaux. Monique Haicault rejette la stérilité de la binarisation traditionnelle, en tenant compte, concrètement et théoriquement, des processus de différenciation sociale de sexe. Son épistémologie « cubique » analyse la triade corps-temps-espace dans le contexte du quotidien et à travers les activités professionnelles, les activités familiales de socialisation, les déplacements urbains et les relations intergénérationnelles. L’utilisation de l’image vidéo donne vie à cette expérience. L’image contribue à montrer comment par leurs comportements, leurs actions, leurs propos et le sens qu’ils donnent à leur expérience, les acteurs sociaux participent de la construction de la société et de sa reproduction dynamique. L’auteure apporte une nouvelle contribution à la socialisation sexuée et à la théorie des rapports sociaux entre sexes et intra-sexe. Elle débouche sur un questionnement qu’il sera désormais difficile de passer sous silence.
Keywords: approches et analyses; corps; discipline; famille; projet charge mentale; rapports sociaux de sexe; sciences humaines; sociologie; thématiques; travail

Au sujet des corps, des techniques et des féminismes dans L'invention du naturel: les sciences et la fabrication du féminin et du masculin - Oudshoorn, Nelly (L'invention du naturel: les sciences et la fabrication du féminin et du masculin, 2000)
Section: 227 pages ; 21 cm
Keywords: 1900-1999; 1990-1999; approches et analyses; corps; cours; discipline; essentialisme; europe; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

Carnal appetites: food, sex, identities - Probyn, Elspeth (Routledge, 2000)
n Carnal Appetites, Elspeth Probyn charts the explosion of interest in food - from the cults that spring up around celebrity chefs, to our love/hate relationship with fast food, our fetishization of food and sex, and the impact of our modes of consumption on our identities. 'You are what you eat' the saying goes, but is the tenet truer than ever? As the range of food options proliferates in the West, our food choices become inextricably linked with our lives and lifestyles. Probyn also tackles issues that trouble society, asking questions about the nature of appetite, desire, greed and pleasure, and shedding light on subjects including: fast food, vegetarianism, food sex, cannibalism, forced feeding, and fat politics.
Keywords: approches et analyses; care; corps; cours; discipline; féminisme pop; lit4700; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sexualité; thématiques; études de genres

Feminism and the body - Schiebinger, Londa (Oxford University Press, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Section: IX, 500 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme